The effects of dietary intervention on fibrosis and biochemical parameters in metabolic-associated fatty liver disease - (:unkn) unknown (My University, 2021)
BACKGROUND: Metabolic-Associated Fatty Liver Disease (MAFLD), affects nearly one quarter of the world's adult population creating large health loads and economic loads in society with no approved pharmacotherapy found yet. The number of studies showing the effect of nutrition on fibrosis accompanying MAFLD are insufficient. This study was planned with the aim of investigating the effect of nutritional treatment on liver injury. METHODS: This research is a prospective, non-medication interventional study completed with 39 participants chosen from MAFLD patients with fibrosis. Post treatment lasting three months, patients had liver stiffness measurements (LSM), anthropometric measurements and biochemical tests repeated. RESULTS: In pre- and post-treatment, there were statistically significant correlations found between LSM with serum gamma glutamyl transferase (GGT) values, and between controlled attenuation parameter (CAP) with body mass index (BMI) and fat mass (p<0.05). Post-treatment, statistically significant improvements were determined in the anthropometric measurements and biochemical findings. Moreover, post-treatment LSM and CAP values showed significant positive correlation compared to pre-treatment (p<0.05). CONCLUSIONS: This study found dietary interventions have an important place within the scope of fibrosis treatment. Preparation and application of medical nutrition treatment suitable for the clinical features of patients and completing correct lifestyle changes has an ameliorating effect on disease prognosis. There is a need for advanced studies with larger sample groups to further enlighten this topic.